Performance of incentive contracts in highway PPP projects in Brazil - Nait Hammou, Amal (2014)
Private-Public Partnerships (P.P.P.) is a new contractual model institutionalized in 2004 that could be used to remedy to the infrastructure deficit in Brazil. In a context of a principal and agent relation, the public partner goal is to give incentives to the private partner in the contract so that their interests are aligned. This qualitative research presents the findings of an empirical study examining the performance of incentive PPP contracts in Brazil in the highway sector. The goal is to explain how the contracting parties can align their interests in an environment of asymmetric information. Literature identified the factors that can influence PPP design and efficient incentive contracts. The study assesses the contribution of these factors in the building of PPP contracts by focusing on the case of the first and only PPP signed in the highway sector in Brazil which is the MG-050. The first step is to describe the condition of the highway network and the level of compliance of the private partner with the contract PPP MG-050. The second step is to explain the performance of the private partner and conclude if the interests of both partners were aligned in contractual aspects. On the basis of these findings and the analysis of the contract, the study formulates suggestions to improve the draft of PPP contracts from the perspective of the incentive theory of contracts.